Supplementary Table S2 from In Vivo Screening Unveils Pervasive RNA-Binding Protein Dependencies in Leukemic Stem Cells and Identifies ELAVL1 as a Therapeutic Target - Ana Vujovic (15207479) (2025)
Table S2 shows sequences of (a) sgRNAs from the RBP screen, (b) sequencing primers, (c) shRNAs and human-targeting sgRNAs, (d) eCLIP oligos.